Unilateral reexpansion pulmonary edema (clinical observations) - Oleg I. Nikitin; Aracbathinia O. Khalimalova; Andrey L. Yudin; Elena A. Yumatova (Клиническая практика)
BACKGROUND: In clinical practice, pulmonary edema still remains one of the threatening conditions with high mortality, despite the sufficiently large attention from the investigators. The classic pulmonary edema is well studied, having its specific x-ray signs, while the unilateral pulmonary edema occurs rarely and causes difficulties in the differential diagnostics performed by the radiologist. CLINICAL CASE DESCRIPTION: The presented material includes cases of ipsi- and contralateral unilateral reexpansion pulmonary edema. These complications have developed as a consequence of rapid evacuation of the pathological content from the pleural cavity. CONCLUSION: Reexpansion pulmonary edema is a rare, though potentially life-threatening condition, which usually occurs as a result of rapid expansion of long-term collapsed lung, for example, in cases of pneumothorax and pleural effusion. The edema may develop several hours after the expansion of the atelectasis.